Complement Components in the Diagnosis and Treatment after Kidney Transplantation—Is There a Missing Link? - Małgorzata Kielar; Agnieszka Gala-Błądzińska; Paulina Dumnicka; Piotr Ceranowicz; Maria Kapusta; Beata Naumnik; Grzegorz Kubiak; Marek Kuźniewski; Beata Kuśnierz-Cabala (Biomolecules, 2021)
Currently, kidney transplantation is widely accepted as the renal replacement therapy allowing for the best quality of life and longest survival of patients developing end-stage renal disease. However, chronic transplant rejection, recurrence of previous kidney disease or newly acquired conditions, or immunosuppressive drug toxicity often lead to a deterioration of kidney allograft function over time. Complement components play an important role in the pathogenesis of kidney allograft impairment. Most studies on the role of complement in kidney graft function focus on humoral rejection; however, complement has also been associated with cell mediated rejection, post-transplant thrombotic microangiopathy, the recurrence of several glomerulopathies in the transplanted kidney, and transplant tolerance. Better understanding of the complement involvement in the transplanted kidney damage has led to the development of novel therapies that inhibit complement components and improve graft survival. The analysis of functional complotypes, based on the genotype of both graft recipient and donor, may become a valuable tool for assessing the risk of acute transplant rejection. The review summarizes current knowledge on the pathomechanisms of complement activation following kidney transplantation and the resulting diagnostic and therapeutic possibilities.